EFFECTS OF LEAF EXTRACTS OF MORINGA OLEIFERA ON REGULATION OF HYPOTHYROIDISM AND LIPID PROFILE - WAZIDA TABASSUM, ARUNA ROSHNI KULLU , M. P. SINHA (The Bioscan, 2013)
The aqueous leaf extract of Moringa oleifera was evaluated for its ameliorative effect in the regulation of thyroidism in rat model. Male albino rats of 120-150 g were treated orally with doses of 500mg/kg body weight (b.w.) and 250 mg/ kg b.w. of aqueous extract of Moringa oleifera leaf. Results show that T3 and T4 were increased and TSH was decreased significantly (p>0.05) at high doses compared to those in the control group. Also, the extract significantly reduced (p<0.05) total cholesterol concentration and low density lipoproteins cholesterol (LDL) concentration in the serum while it had no significant effect on serum High density lipoprotein (HDL) cholesterol concentration at all doses administered when compared with controls. The results of this study suggest that the extract may have beneficial effect on serum cholesterol concentration and a stimulant to thyroid functions.